2018
DOI: 10.1101/263988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Task errors contribute to implicit remapping in sensorimotor adaptation

Abstract: Perturbations of sensory feedback evoke sensory prediction errors (discrepancies between 13 predicted and actual sensory outcomes of movements), and reward prediction errors (discrepancies 14 between predicted rewards and actual rewards). Sensory prediction errors result in obligatory remapping 15 of the relationship between motor commands and predicted sensory outcomes. The role of reward 16 prediction errors in sensorimotor adaptation is less clear. When moving towards a target, we expect to 17 obtain the re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that changes in sensorimotor mapping can be driven purely by reinforcement learning (Izawa and Shadmehr 2011;Shmuelof et al 2012;Therrien et al 2016), which can occur without awareness (Alamia et al 2016). Furthermore, recent studies have shown that reward signals can modulate the extent of implicit motor learning (Kim et al 2018;Leow et al 2018;Reichenthal et al 2016). At the current time, whether modulation of reward can alter the tuning of the SLR is not known.…”
Section: Implicit Motor Learning Drives the Partial Adaptation Of Slr Tuning During Visuomotor Rotationsmentioning
confidence: 95%
“…Previous studies have shown that changes in sensorimotor mapping can be driven purely by reinforcement learning (Izawa and Shadmehr 2011;Shmuelof et al 2012;Therrien et al 2016), which can occur without awareness (Alamia et al 2016). Furthermore, recent studies have shown that reward signals can modulate the extent of implicit motor learning (Kim et al 2018;Leow et al 2018;Reichenthal et al 2016). At the current time, whether modulation of reward can alter the tuning of the SLR is not known.…”
Section: Implicit Motor Learning Drives the Partial Adaptation Of Slr Tuning During Visuomotor Rotationsmentioning
confidence: 95%